Sibu Rural District Council (SRDC) / Sendy Yong - Yong, Sendy (University Technology MARA Sarawak, 2014)
Sibu is an inland town, and the capital of Sibu’s District (229.8 square kilometres) in Sibu Division, Sarawak, East Malaysia. It is located at the confluence of the Rajang and Igan Rivers, some 60 kilometres from the ocean and approximately 183.3 kilometres east-north-east of the state capital Kuching. The population is dominated by Chinese especially the Fuzhou as well as indigenous Melanau, Malay, and Iban. The town population (year 2010) is 257,800. Sibu is the main tourist gateway to the Upper Rajang River, with its small riverine towns and its many Iban and Orang Ulu longhouses.